PENINGKATAN KOMPETENSI GURU MTs KECAMATAN BATEALIT KABUPATEN JEPARA DALAM MERANCANG MODEL PROJECT BASE LEARNING MELALUI WORKSHOP - MUSTA’IN MUSTA’IN (ACADEMIA: Jurnal Inovasi Riset Akademik, 2021)
This study aims to describe the process of developing a Project Based Learning Model through workshops, as well as improving the competence of MTs Teachers in Batealit District in Jepara Regency in developing Project Based Learning Models. The research was conducted in two cycles and each cycle consisted of four stages, namely: planning, implementation, observation and reflection. From the results of the analysis obtained information that there is an increase in the ability of MTs teachers in Batealit District in Jepara Regency in designing Project Based Learning Models. The increase was shown (1) the ability of MTs Teachers in Batealit District in Jepara Regency in designing the characteristics of the Project Based Learning Model from 20% in the first cycle to 100% in the second cycle; (2) the ability of MTs Teachers in Batealit District in Jepara Regency in identifying Project Based Learning Model constraints from 27% in the first cycle to 100% in the second cycle; (3) the ability of MTs Teachers in Batealit District in Jepara Regency in designing the objectives of the Project Based Learning Model, from 27% in the first cycle to 100% in the second cycle; (4) the ability of MTs Teachers in Batealit District in Jepara Regency in compiling the steps of the Project Based Learning Model, from 20% in the first cycle to 100% in the second cycle; (5) The ability of MTs teachers in Batealit District in Jepara Regency in designing Project Based Learning Models, from 17% in the first cycle to 100% in the second cycle. Other information shows that the response of MTs teachers in Batealit Subdistrict in Jepara Regency in participating in the workshop process in order to design a Project Based Learning Model 67% responded very well and 33% responded well. This shows that the MTs teachers in Batealit District in Jepara Regency really expect a workshop to improve their competence. ABSTRAKPenelitian ini bertujuan untuk mendeskripsikan proses pengembangan Model Project Based Learning melalui workshop, serta meningkatkan kompetensi Guru MTs Kecamatan Batealit di Kabupaten Jepara dalam menyusun Model Project Based Learning. Penelitian dilakukan dengan dua siklus dan masing-masing siklus terdiri atas empat tahapan, yakni: perencanaan, pelaksanaan, observasi dan refleksi. Dari hasil analisis diperoleh informasi bahwa terjadi peningkatan keamampuan Guru MTs Kecamatan Batealit di Kabupaten Jepara dalam merancang Model Project Based Learning. Peningkatan itu ditunjukkan (1) kemampuan Guru MTs Kecamatan Batealit di Kabupaten Jepara dalam merancang karakteristik Model Project Based Learning dari 20% pada siklus I menjadi 100% pada siklus II; (2) kemampuan Guru MTs Kecamatan Batealit di Kabupaten Jepara dalam mengidentifikasi kendala Model Project Based Learning dari 27% pada siklus I menjadi 100% pada siklua II; (3) kemampuan Guru Guru MTs Kecamatan Batealit di Kabupaten Jepara dalam merancang tujuan Model Project Based Learning, dari 27% pada siklus I menjadi 100% pada siklus II; (4) kemampuan Guru MTs Kecamatan Batealit di Kabupaten Jepara dalam menyusun langkah-langkah Model Project Based Learning, dari 20% pada siklus I menjadi 100% pada siklus II; (5) Kemampuan Guru MTs Kecamatan Batealit di Kabupaten Jepara dalam membuat rancangan Model Project Based Learning, dari 17% pada siklus I menjadi 100% pada siklus II. Informasi lain menunjukkan bahwa respon Guru MTs Kecamatan Batealit di Kabupaten Jepara dalam mengikuti proses workshop dalam rangka merancang Model Project Based Learning 67% merespon sangat baik dan 33% merespon baik. Ini menunjukkan bahwa Guru MTs Kecamatan Batealit di Kabupaten Jepara sangat mengharapkan adanya workshop dalam meningkatkan kompetensi mereka.